Hypovitaminosis D: An Emerging new Risk Factor of Coronary Artery Disease (Bangladesh Journal of Medical Biochemistry, 2025)
Coronary artery disease (CAD) is one of the most important medical and public health problem and leading cause of death throughout the world. It is often premature in onset, rapidly progressive and angiographically more severe. The underlying pathophysiology is poorly understood. Genetic predisposition high prevalence of metabolic syndrome and other conventional risk factors play important role. Some new risk factors inclauding hypovitaminosis D, chronic arsenicosis, air pollution may play unique role. Among the new predictors of coronary artery disease, the focus has been shifted to vitamin D. Because hypovitaminosis D may play unique role in the pathogenesis of coronary artery disease, promoting accelerated atherosclerosis and subsequent cardiovascular events. Recent researches have highlighted vitamin D deficiency as an emerging risk factor for coronary artery disease, in addition to conventional and genetic risk factors. In this review, we will provide an overview on the currently available evidence supporting the relationship between hypovitaminosis D and coronary artery disease and its possible underlying mechanisms.Bangladesh J Med Biochem 2019; 12(1 and 2): 17-25